2011
DOI: 10.1007/s00296-011-2186-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Iranian versions of the bath ankylosing spondylitis disease activity index (BASDAI), the bath ankylosing spondylitis functional index (BASFI) and the patient acceptable symptom state (PASS) in patients with ankylosing spondylitis

Abstract: The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Bath Ankylosing Spondylitis Functional Index (BASFI) are widely used instruments in assessment of patients suffering from ankylosing spondylitis (AS). The Patient Acceptable Symptom State (PASS) is regarded as a target for patients' well-being. The aim of this study was to translate and adapt BASDAI, BASFI and PASS into the Iranian official language, Farsi, and evaluate their reliability and validity. Ninety patients with AS were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…[7,[13][14][15][16][17] However, the relationship between smoking and radiographic severity has not been consistent in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]18] To our knowledge, the first survey which exposed the connection between smoking and AS patient outcomes was by Averns et al [15] in 1996. This investigation was included AS patients with a median duration of 20 years, and the authors found significant differences between smokers and non-smokers with regard to the finger-floor distance, Schober's test, total spinal involvement, occiput-to-wall distance, functional status, stiffness, and spinal radiographic damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,[13][14][15][16][17] However, the relationship between smoking and radiographic severity has not been consistent in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]18] To our knowledge, the first survey which exposed the connection between smoking and AS patient outcomes was by Averns et al [15] in 1996. This investigation was included AS patients with a median duration of 20 years, and the authors found significant differences between smokers and non-smokers with regard to the finger-floor distance, Schober's test, total spinal involvement, occiput-to-wall distance, functional status, stiffness, and spinal radiographic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Validated Iranian versions of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Quality of Life (ASQoL) questionnaires were applied to assess the disease activity and QoL, respectively. [9][10][11] In addition, the Bath Ankylosing Spondylitis Metrology Index (BASMI) was used for measuring spinal mobility. [12] The BASDAI, ASQoL, and BASMI scores were also calculated at approximately the same time for all of the patients during the study for uniformity.…”
Section: Methodsmentioning
confidence: 99%
“…Validated Persian version of BASFI (from 0: performed without difficulty to 10: impossible to perform), BASDAI (from 0: no activity to 10: maximum activity) and ASQoL (from 0: the best quality to 18: the worst quality) were used. 15,16 All measurements were performed at the same time of the day and by a single examiner for measurement uniformity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, our research only focused on TNF-α, VEGF, and MMP-3, and thus cannot fully illustrate the differentiation of synovial fibroblasts (Hamed et al, 2004;Crisostomo et al, 2007). Other factors such as IL-12B might also be related to AS progression (Kolomecki et al, 2001;Bidad et al, 2012). These questions require further analysis.…”
Section: Discussionmentioning
confidence: 92%